Археологічні розвідки в м. Харків і Харківській обл. у 2008 р. - Шрамко, І.Б.; Голубєва, І.В.; Задніков, С.А.; Окатенко, В.М.; Пеляшенко, К.Ю. (Археологічні дослідження в Україні, 2009)
The paper presents the results of scientific archaeological examinations made in 2008 on the territory of Kharkiv city and Kharkiv Oblast. The important information has been obtained on the life of local habitants during the various periods: from the Bronze Age to the Late Mediaeval epoch.